The Role of Knowledge Sharing, Employee Competency, and Employee Empowerment to Improve Employee Performance - Hanani, Fara Sofia; Juniarto, Galuh; Suparmi, Suparmi (Faculty of Economics and Business UNTAG Semarang, 2024)
The public still complains about the performance of employees in Demak District, Demak Regency. Based on the research gap in previous research, this study aims to empirically test the role of knowledge sharing, employee competency, and employee empowerment to improve the employee's performance. The sample used in this research was 52 employees of Demak District, Central Java, taken using the census. The data was collected through questionnaires and data analysis using SPSS 25, including validity, reliability, classical assumption tests, multiple linear regression, t-test, F-test, and R2 test. The results stated that sharing knowledge, employee competency and employee empowerment positively and significantly affected the employee’s performance. The implications state that employees should maximize their ability to convey their knowledge to other employees, prioritize the values of honesty, openness in work, and responsibility.